Sexual dimorphism and sex identification in the South American culpeo fox, Pseudalopex culpaeus (Carnivora: Canidae) - Travaini, Alejandro (2000)
Sexual dimorphism is analysed in skulls of the culpeo fox, Pseudalopex culpaeus, through multivariate and univariate approaches. The species shows a moderate level of sexual dimorphism with most cranial variables being, on average, 5% larger in males. Equations are obtained for inferring the sex of skulls of juvenile, subadult and adult culpeo foxes. The equations are based on a reduced set of variables obtained from stepwise discriminant analyses by age class on skull measurements. The discriminant power of all functions is estimated on the basis of a jackknife reclassification procedure. Correct classification is higher than 85% for both sexes, and is similar to, or higher than, the values reported for other foxes. The use of the discriminant function pooling subadult and adult skulls is recommended because it shows a high percentage of correct classification without the necessity of ascribing a collected skull to the subadult or adult age class before sex estimation. The equations provide an easy method to estimate the sex ratio of wild populations of this furbearer species using the abundant carcasses discarded throughout north-western Patagonia as a result of the intense hunting of the species. The information on sex ratios will help in the study of population dynamics and when monitoring the harvest of culpeo foxes.